UPAYA PENINGKATAN MUTU MENGAJAR GURU PRODUKTIF MELALUI SUPERVISI AKADEMIK KETUA PROGRAM KEAHLIAN DI SMK NEGERI 2 KOTA PROBOLINGGO - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
This study aims to determine the efforts to improve the teaching quality of productive teachers through the academic supervision of the head of the expertise program at SMK Negeri 2 Probolinggo City. The results showed that the academic supervision delegation system from the principal to the head of the expertise program at SMK Negeri 2 Probolinggo City. The head of SMK Negeri 2 Probolinggo City has formed a supervisory team consisting of the Head of the Study Program and senior teachers. Academic supervision carried out by the head of the expertise program to the expertise program teacher (productive) at SMK Negeri 2 Probolinggo City, the principal has prepared an academic supervision program plan, requested a report from the head of the program, and followed up on the results of supervision as it should be. The teaching quality of productive teachers at SMK Negeri 2 Probolinggo City has improved both in terms of administrative and process. The factors that support the implementation of academic supervision of the principal of SMK Negeri 2 Probolinggo City are the high professionalism of the principal, high supervisor competence (through the head of the program), teachers who on average are ready to be supervised, especially productive teachers, principals are able to create a good relationship pattern with the principal. all components of the school, the principal is able to overcome obstacles in the implementation of academic supervision carried out by the head of the program, and the school infrastructure is sufficient and representative for teaching and learning activities.